ANALYSIS OF DERMATOSES IN PREGNANCY: A NARRATIVE REVIEW OF THE LITERATURE (International Seven Journal of Multidisciplinary, 2024)
Objective: To analyze dermatoses during pregnancy. Bibliographic Review: Pregnancy is a complex physiological state that promotes several changes in the woman's body, such as immunological, metabolic, hormonal and vascular changes. It is possible to observe, during the gestational period, dermatoses that may appear or worsen due to the various transformations resulting from this period. Dermatoses essentially associated with pregnancy (DEG) encompass a group of diseases that appear in the pregnancy or postpartum period. Other dermatoses, on the other hand, can be directly affected by pregnancy, improving, having an unpredictable behavior, but usually end up exacerbating this pre-existing pathology. Final considerations: It should be noted that dermatological diseases typical of pregnancy may be restricted to the skin and mucous membranes, or express a systemic impairment, such as pruritus gravidarum, as a result of cholestasis. Immunological diseases represent a problem during pregnancy, due to the possibility of their worsening or the need for an appropriate choice of drugs used.